Atomistically kinetic simulations of carbon diffusion in ɑ-iron with point defects - Hồ, Ngọc Nam (2020)
The real lattice is not perfect but contains many types of defects, which can be referred to as vacancy, dislocation, or grain boundary. While vacancy is well known as a typical case of point defect and also a simple case which we can consider. Study about the vacancy case in BCC structure of iron will help us understand clearly about the role and the effects of vacancy to the diffusion and clustering of carbon in iron matrix. The cause of the interaction between carbon and metals has a tremendous scientific and technological interest which has essential effects on the yield stress and the subconsequent mechanical properties and also a broad range of implications in the scope of material science. Research on atomic carbon concentration dissolved in iron as well as its distribution and diffusion in iron plays a vital role in making a view insight of phenomena such as carbide precipitation, martensite aging, and ferrite transformation. The restriction of system size when calculating using First principle method causes Molecular Dynamic (MD) to be a reasonable substitute for large systems. However, the accuracy of MD simulations largely depends on the choice of interatomic potential. Recently, Nguyen et al. developed a new interatomic potential to describe the interaction of Fe-C system based on the analytic bond-order potential (ABOP) formalism, which gives good results in describing minimum energy path (MEP) of carbon with T site found as a transition point